2021
DOI: 10.1002/lary.29687
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Unanticipated Admission After Outpatient Endoscopic Sinonasal Surgery

Abstract: Objectives/Hypothesis: To identify factors that may increase the risk of unplanned admission following elective outpatient endoscopic sinonasal surgery (ESS).Study Design: Retrospective analysis of the National Surgical Quality Improvement Program (NSQIP).Methods: All cases of ESS were extracted from the 2010 to 2018 NSQIP database using Current Procedural Terminology codes. Only cases coded as outpatient, elective, and nonemergent procedures were included. Unplanned admissions were defined as cases with a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…However, this result may be more representative of this specific NIS‐based cohort, as other studies investigating the role of patient sex on complication rates following TSPS showed no difference 9,26 . Moreover, older patients have been shown to experience higher rates of postoperative complications following TSPS, paralleling our study's findings 27 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, this result may be more representative of this specific NIS‐based cohort, as other studies investigating the role of patient sex on complication rates following TSPS showed no difference 9,26 . Moreover, older patients have been shown to experience higher rates of postoperative complications following TSPS, paralleling our study's findings 27 …”
Section: Discussionsupporting
confidence: 83%
“…9,26 Moreover, older patients have been shown to experience higher rates of postoperative complications following TSPS, paralleling our study's findings. 27 Our results indicate that treatment at HVFs correlates with lower rates of PSI events, poor outcomes, and in-hospital mortality when compared with LVFs and MVFs. As PSI events are representative of postoperative complications, the results suggest that HVFs offer superior outcomes and postoperative care for patients with TSPS.…”
Section: Discussionmentioning
confidence: 55%